Numerical investigation of the effect of carotid bifurcation stenosis degree on pulsatility characteristics - Liu, Chao; Wu, Gao; Xu, Jianxin; Xiao, Qingtai; Wang, Hua (Frontiers in Physiology, 2023)
Arterial bifurcations are regions that are susceptible to hemodynamic effects and thrombus formation. In the current study, the hemodynamic effects of a simplified 3D model of an arterial bifurcation were simulated using the commercial computational fluid dynamics software FLUENT. The non-Newtonian properties of blood were modeled using the Carreau model, and the pulsation dynamics and heat transfer characteristics of blood at different degrees of stenosis in the arterial bifurcation were analyzed. The results indicate that arterial stenosis caused by a thrombus when the pulsation velocity reaches its peak has an essential impact on blood transport. The stenosis of the bifurcation increases the peak pulsatile flow pressure drop, and each 0.5 mm stenosis of the arterial bifurcation increases the mean wall shear stress of the bifurcated segment by approximately 0.25 Pa. From the heat transfer perspective, arterial stenosis has little effect on the heat transfer coefficient. The heat transfer coefficient measured inside the bifurcation is much larger than that measured outside the bifurcation. The stenosis of the arterial bifurcation causes an increase in the mean velocity of the arterial cross-section, and the volume-averaged absolute vorticity is introduced to quantify the secondary flow effect during the pulsation cycle, where the arterial stenosis causes an increase in the mean absolute vorticity at pulsation velocity and accelerates the decay of the vorticity at uniform velocity. In this paper, the hemodynamics of carotid bifurcation pulsation is analyzed in conjunction with flow field properties to reveal the flow field dynamics factors and heat transfer characteristics of local stenosis of the carotid bifurcation and to conduct an exploratory study for the diagnosis and treatment of carotid bifurcation thrombosis.